Impact(s) of doctoral degrees held by faculty members in Portuguese higher education - Leitão, João (2013)
In order to verify the impact(s) of doctoral programs processes of faculty members in higher education in Portugal. we applied a questionnaire survey to the completed PhD of teachers. This study is based on a questionnaire survey to the doctoral degrees of faculty members in Portuguese higher education, completed between 2007 and 2012, the survey was held between April 16 and May 6, 2012, to all teachers in Portuguese higher education having quickly reached 1001 answers that we briefly analyze here. It appears that in this period of analysis, there were many faculty members who have successfully completed their doctoral process, meeting the quality standards that enable the integration of higher education in the Portuguese panorama of internationalization, especially in view of the requirements of the Bologna process.